A STEDable BF2-Azadipyrromethene Fluorophore for Nuclear Membrane and Associated Endoplasmic Reticulum Imaging - Anaïs C. Bourgès; Massimiliano Garre; Dan Wu; Donal F. O’Shea (Membranes)
The endoplasmic reticulum and the internal nuclear compartments are intrinsically connected through the nuclear membrane, pores and lamina. High resolution imaging of each of these cellular features concurrently remains a significant challenge. To that end we have developed a new molecular nuclear membrane-endoplasmic reticulum (NM-ER) staining fluorophore with emission maxima at 650 nm. NM-ER is compatible with fixed and live cell imaging and stimulated emission depletion microscopy (STED) showing significant improvement in resolution when compared to comparable confocal laser scanning microscopy. The imaging versatility of NM-ER was illustrated through its compatible use with other fluorophores for co-imaging with DNA, nuclear pores and lamina allowing cellular abnormalities to be identified. NM-ER alone, or in use with other nuclear region labels could be an important tool for the investigation of nuclear transport and associated cellular processes.